2006
DOI: 10.1136/gut.2005.083014
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori outer membrane proteins and gastroduodenal disease

Abstract: Background and aims: A number of Helicobacter pylori outer membrane proteins (OMPs) undergo phase variations. This study examined the relation between OMP phase variations and clinical outcome. Methods: Expression of H pylori BabA, BabB, SabA, and OipA proteins was determined by immunoblot. Multiple regression analysis was performed to determine the relation among OMP expression, clinical outcome, and mucosal histology.Results: H pylori were cultured from 200 patients (80 with gastritis, 80 with duodenal ulcer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
197
2
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(207 citation statements)
references
References 30 publications
6
197
2
2
Order By: Relevance
“…Nonetheless, approximately half of the studies have suggested a correlation between babA2-positive H pylori in Western countries and increased risk of developing significant clinical outcomes [38,[44][45][46]52] and are in agreement with protein data as described above [31,33,34] . The prevalence of clinical isolates with a non-functional babA2 gene without production of BabA protein may be low and negligible in some studies.…”
Section: Detection Of Functional Baba Genesupporting
confidence: 68%
See 1 more Smart Citation
“…Nonetheless, approximately half of the studies have suggested a correlation between babA2-positive H pylori in Western countries and increased risk of developing significant clinical outcomes [38,[44][45][46]52] and are in agreement with protein data as described above [31,33,34] . The prevalence of clinical isolates with a non-functional babA2 gene without production of BabA protein may be low and negligible in some studies.…”
Section: Detection Of Functional Baba Genesupporting
confidence: 68%
“…There currently are only a few studies that correlate the importance of BabA with clinical outcomes using immunoblot analyses [31,33,34] . My group recently performed large scale studies of 520 geographically diverse patients presenting with different clinical symptoms to evaluate BabA status by immunoblot analysis [31] .…”
Section: Baba Le B Binding Activity and Clinical Outcomesmentioning
confidence: 99%
“…Immunoblotting-Anti-AlpA (AK214) (8), anti-AlpB (AK262) (9), anti-BabA (AK277) (18), and anti-OipA antisera (AK282) (19) were used as primary antibodies at a 1:5,000 dilution. Anti-CagA and anti-VacA antibodies (Austral Biologicals, San Ramon, CA) were used at a 1:3,000 dilution.…”
Section: Methodsmentioning
confidence: 99%
“…To minimize the risk of phase variations, all H pylori samples were obtained from a single bacterial colony that was passaged in vitro less than 4 times. 26 The control strain was strain J99, 27 which contains a babA gene and possesses Le b binding ability. 3 We also used strain 26695, 23 which contains a babA gene but does not bind to Le b , 3 and strain TN2GF4, 28 which contains a babA gene and possesses Le b binding ability.…”
Section: Helicobacter Pylorimentioning
confidence: 99%